“Now the voice of Isaiah the prophet…”: on the unusual attribution of Old Testament prophecy in Ancient Church hymnography - Nikolay Serebryakov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The article considers an unusual case of "incorrect" attribution of the words of the prophet Malachi to the prophet Isaiah on the example of two hymns of the service of the Nativity of St. John the Baptist (24 June), written by St. John of Damascus (7th – 8th centuries) and St. Kassia (9th century). According to the author, this attribution is due to the fact that the hymnographers did not directly use the text of the prophetic book, but quoted this prophecy in the transmission of Mark 1. 2. The form of the quoted Gospel text corresponded to the Alexandrian text-type of New Testament manuscripts, where the prophet Isaiah is indicated as the author of the prophecy quoted in Mark 1. 2. The following is a discussion of the possible reasons for the use by the hymnographers in question of the New Testament text instead of the Old Testament text: (1) the words of Mark 1. 2 (and the parallels in Matt 11. 10 and Luke 7. 17) may have been more familiar to Christians of that time than their Old Testament prototype; moreover (2) the Gospel restatement of the prophecy revealed its meaning, pointing to the divinity of Jesus Christ, as well as clarifying the sense of John the Baptist's ministry. The reasons for the use of Mark 1. 2 (despite the problematic character of these apostolic words because of the unusual attribution of prophetic words) could be the prominent position of this verse at the beginning of the Gospel of Mark and its connection with the proclamation there of the messianic dignity of Jesus Christ, as well as the fact that the hymnographers continued the patristic tradition of advocacy of the correctness of the words of Mark 1. 2. At the end of the article some peculiarities of the use and interpretation of the text of the Holy Scriptures in Byzantine hymnography are pointed out on the basis of the material considered. First of all, it is the use of the Old Testament words in their New Testament version, because this version of the words is better known to Christians and has already been interpreted by the apostles themselves. It is no less important that in their use and interpretation of the biblical text the hymnographers clearly followed the preceding patristic exegetical tradition, including trust in the words of the Holy Scripture.